2017
DOI: 10.1038/s41598-017-05252-w
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the presence of fish farm-derived organic matter at the seafloor using stable isotope analysis of phospholipid fatty acids

Abstract: The expansion of global aquaculture activities is important for the wellbeing of future generations in terms of employment and food security. Rearing animals in open-exchange cages permits the release of organic wastes, some of which ultimately reaches the underlying sediments. The development of rapid, quantitative and objective monitoring techniques is therefore central to the environmentally sustainable growth of the aquaculture industry. Here, we demonstrate that fish farm-derived organic wastes can be rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Likewise in our study, the sedimentary OM was depleted under fish cages compared to the reference, in Tasmania (Ye et al, 1991). Mayor et al (2017) reported that phospholipid fatty acid (PLFA) extracted from surficial sediments in five Scottish fish farms also showed a trend to more depleted δ 13 C values with increasing farm size and production. Contrary, Yokoyama et al (2006), , and Callier et al (2013) did not find a clear trend in δ 13 C of sedimentary OM in relation to fish farming in Japan, Spain, Greece, Italy, and Ireland.…”
Section: Processes In the Sediment In Relation To Fish Farmingsupporting
confidence: 71%
See 1 more Smart Citation
“…Likewise in our study, the sedimentary OM was depleted under fish cages compared to the reference, in Tasmania (Ye et al, 1991). Mayor et al (2017) reported that phospholipid fatty acid (PLFA) extracted from surficial sediments in five Scottish fish farms also showed a trend to more depleted δ 13 C values with increasing farm size and production. Contrary, Yokoyama et al (2006), , and Callier et al (2013) did not find a clear trend in δ 13 C of sedimentary OM in relation to fish farming in Japan, Spain, Greece, Italy, and Ireland.…”
Section: Processes In the Sediment In Relation To Fish Farmingsupporting
confidence: 71%
“…The stable isotopes were used to reveal the impact of fish rearing on the environment in several studies (Ye et al, 1991;Sara et al, 2006;Landrum and Montoya, 2009). According to Mayor et al (2017) the analysis of the carbon stable isotopes of bulk sediment represents an alternative and fast approach to quantify the fate of fish farmderived organic matter. Moreover, the isotopic signature of the fish feed pellets can be distinct from the local sources, as they are composed of terrestrial material and fishmeal originating from other seas (Moreno-Rojas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise in our study, the sedimentary OM was depleted under fish cages compared to the reference, in Tasmania (Ye et al, 1991). Mayor et al (2017) reported that phospholipid fatty acid (PLFA) extracted from surficial sediments in five Scottish fish farms also showed a trend to more depleted δ 13 C values with increasing farm size and production. Contrary, Yokoyama et al (2006), Holmer et al (2007, and Callier et al (2013) did not find a clear trend in δ 13 C of sedimentary OM in relation to fish farming in Japan, Spain, Greece, Italy, and Ireland.…”
Section: Processes In the Sediment In Relation To Fish Farmingsupporting
confidence: 71%
“…The stable isotopes were used to reveal the impact of fish rearing on the environment in several studies (Ye et al, 1991;Sarà et al, 2004;Sara et al, 2006;Holmer et al, 2007;Landrum and Montoya, 2009). According to Mayor et al (2017) the analysis of the carbon stable isotopes of bulk sediment represents an alternative and fast approach to quantify the fate of fish farmderived organic matter. Moreover, the isotopic signature of the fish feed pellets can be distinct from the local sources, as they are composed of terrestrial material and fishmeal originating from other seas (Moreno-Rojas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For FA analysis, fatty acid methyl esters (FAME) are created by homogenising tissue samples with chloroform and methanol and rinsing off non-lipid impurities. 98,170,174,175 The total lipids in FAME are then separated and quantified through a process such as gas-liquid chromatography (GLC), where peak retention times are measured against known FAME standards and FA composition can subsequently be expressed as a percentage of total lipid content. 164,175,176 These FA proportions present in the tissues can then be compared to feed pellets used at the aquaculture site to determine if wild species have been consuming significant amounts of fish feed.…”
Section: Fatty Acid and Stable Isotope Analysis (And Other Tracers)mentioning
confidence: 99%